Nurse Retention in the Acute Care Setting - Thomas, Emma Parry (My University, 2024)
Nursing burnout and turnover intention are growing issues, largely impacted by the Covid-19 pandemic, yet ones that were prevalent before this worldwide health crisis and will persist in the coming years. Strategies to intervene are key in order to maintain a strong workforce in the acute care setting. Signs of burnout such as emotional and physical fatigue, decreased alertness at work, and desire to leave the profession increased following a season of working during the pandemic. Among a large sample of RNs that experienced this increased workload, over half reported feeling at the end of their rope, fatigued, or burned out at least a few times a week if not every day. With high levels of burnout, there is potential for an increase in turnover intention and subsequent further decline in nurses unless solutions are quickly enacted. This integrative review explores the current literature available on the causes and consequences of burnout as well as strategies to prevent and reduce the impacts of burnout and turnover intention on the nursing profession. Main causes of nursing burnout include high nurse to patient ratios and interpersonal strain such as lack of support from leaders and tumultuous staff relationships. The consequences of burnout and turnover intention include poor patient outcomes and declines in the mental and physical health of nurses. Strategies to improve nurse retention were categorized into main themes and their prevalence among the research articles was analyzed. These categories are leadership (41%), organizational culture (45%), interprofessional relationships (43%), and self-care activities (38%). Strategies to reduce burnout include policies on staffing ratios and allowing nurses to have organizational power. Like burnout, strategies to reduce turnover intention happen at both the organizational and personal levels.
Keywords: burnout, turnover intention, workforce retention